MODIFIKASI ZAT PENGATUR TUMBUH DALAM BUDIDAYA JARINGAN UNTUK PERBANYAKAN BIBIT TEBU (Saccharum officinarum) - Supalal . (Bioma : Jurnal Ilmiah Biologi, 2015)
The aim was to obtained growth regulator effect in sugarcane multiplication?óÔé¼Ôäós method. This research was expected to support particular sugarcane seedlings progam. The sugarcane?óÔé¼Ôäós clone used VMC as explan for this research. The explan used medium MS0, MS + 0,5 mg/l BAP, MS + 1 mg/l BAP + 0,5 mg/l IBA, MS + 1,5 mg/l BAP + 0,5 mg/l IBA. It?óÔé¼Ôäós repetead 3 times and consisted 3 samples. Research?óÔé¼Ôäós parameters observed percentage and growing shoot?óÔé¼Ôäós speed, bud?óÔé¼Ôäós number, and shoots. MS + 1,5 mg/l BAP + 0,5 mg/l IBA had the best growthed and shoot?óÔé¼Ôäós number among the other concetration; which was showed 66,67%.Keywords: tissue culture, growth regulator, sugarcane shoot